Industrialisasi Produk Halal Negara Minoritas Muslim - Muchamad Iqbal Fatah; Moch Mahsun (International Consortium of Islamic Researchers (ICONIRs) CV. Branded Tech Indonesia, 2024)
Attention to halal products for Muslims in the world is increasingly growing, especially in countries with minority Muslim populations. Labels for halal food and beverage products for Muslim minority countries are certainly very much needed because Islamic doctrine teaches its people to consume halal food and drinks. There are several Muslim minority countries in the world such as Brazil, Australia, Taiwan, Russia, Thailand, the Philippines and several other Muslim minority countries that require acceleration in the practice of Islam for Muslims in minority countries. The policy of a country as a determinant of the direction of the formation of social identity of the lives of adherents between diverse communities is a necessity. The presence and role of halal certification institutions that provide halal product guarantees (JPH) such as in Indonesia, is a concrete example that is a hope and opportunity for Muslims in minority countries. It is not surprising that since 2022 the Indonesian Ministry of Religion has provided assessments for foreign halal institutions (LHLN) in several countries, such as South Korea, New Zealand, the United States and others. This article describes how the industrialization of halal products in Muslim minority countries; between opportunities and challenges? Through qualitative methods with a literature study approach, this article is expected to provide a constructive contribution to the development of scientific studies on Islamic economics, especially in the discourse on halal product development.